Somatic mosaicism of the PI3K‐AKT‐MTOR pathway is associated with hemimegalencephaly in fetal brains. Issue 2 (3rd November 2022) - Itoh, Kyoko; Pooh, Ritsuko; Shimokawa, Osamu; Fushiki, Shinji
Abstract : It is known that somatic activation of PI3K–AKT–MTOR signaling causes malformations of cortical development varying from hemimegalencephaly to focal cortical dysplasia. However, there have been few reports of fetal cases. Here we report two fetal cases of hemimegalencephaly, one associated with mosaic mutations in PIK3CA and another in AKT1 . Both brains showed polymicrogyria, multiple subarachnoidal, subcortical, and subventricular heterotopia resulting from abnormal proliferation of neural stem/progenitor cells, cell differentiation, and migration of neuroblasts. Scattered cell nests immunoreactive for phosphorylated‐S6 ribosomal protein (P‐RPS6) (Ser240/244) were observed in the polymicrogyria‐like cortical plate, intermediate zone, and arachnoid space, suggesting that the PI3K–AKT–MTOR pathway was actually activated in these cells. Pathological analyses could shed light on the mechanisms involved in disrupted brain development in the somatic mosaicism of the PI3K‐AKT–MTOR pathway.